2006
DOI: 10.1353/rhe.2006.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Statewide Articulation Agreements on the Probability of Transfer: A Preliminary Policy Analysis

Abstract: The paper poses the following research question: Does the existence of statewide articulation agreements increase the probability of vertical transfers from two-year to four-year colleges? Stated differently, is there a difference in transfer rates between those states with statewide mandates versus those without such policies? Additionally, this paper culls from postsecondary data on individual characteristics to identify other factors impacting the probability of transferring and to suggest policy considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 43 publications
0
67
0
Order By: Relevance
“…A report by the Public Policy Institute of California (Moore & Shulock, 2014) shared concerns about the slow and delayed implementation process. As has been documented in Arizona, New Jersey, Ohio, and Washington (Kisker, Wagoner, & Cohen, 2011), reports on California's ADT plan found that the primary focus of implementation had been the measurable outcomes of the policy, such as the number of transfer degrees created, improved time-todegree, enhanced transfer rates, and greater degree completion (Anderson et al, 2006;Roksa & Keith, 2008).…”
Section: Legislating the Transfer Process In Californiamentioning
confidence: 91%
See 2 more Smart Citations
“…A report by the Public Policy Institute of California (Moore & Shulock, 2014) shared concerns about the slow and delayed implementation process. As has been documented in Arizona, New Jersey, Ohio, and Washington (Kisker, Wagoner, & Cohen, 2011), reports on California's ADT plan found that the primary focus of implementation had been the measurable outcomes of the policy, such as the number of transfer degrees created, improved time-todegree, enhanced transfer rates, and greater degree completion (Anderson et al, 2006;Roksa & Keith, 2008).…”
Section: Legislating the Transfer Process In Californiamentioning
confidence: 91%
“…Yet, in practice, the transfer function has not worked as intended, and has become more complex and unclear over the years (Ignash & Townsend, 2001;Mosholder & Zirkle, 2007). Over the last decade, research has indicated a decline in transfer rates from community colleges to four-year institutions (Anderson, Sun, & Alfonso, 2006;Kisker et al, 2012;Levin & Kanter, 2013;Townsend, 2007).…”
Section: Community College and State Transfer Agreementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students from low socio-economic backgrounds, minority students, and non-traditional students turned to local community colleges for a chance at upward career and social mobility (Brint & Karabel, 1989;Meier, 2013). However, there is growing evidence that community colleges of the past served students well, but community colleges of the present are faring poorly in terms of the persistence and retention of their students (Anderson, Sun, & Alfonso, 2006;Fike & Fike, 2008).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…6 The relationship between institutional or disciplinary culture, race, and ethnicity is especially relevant to racial and ethnic minorities that are even more underrepresented in STEM than they are in most other fields. 7,8 In 2014, 10.5 million foreign-born persons had a college degree or higher, representing about twenty-nine percent of the total 36.7 million U.S. foreign-born population ages 25 and over. Foreign-born Americans are earning STEM degrees in disproportionately large numbers, compared to the native-born U.S. population.…”
mentioning
confidence: 99%